Polysomnography findings and risk factors for sleep-disordered breathing in patients with systemic sclerosis - Ebru Çakır Edis,; Renginar Mutlucan Eraslan,; Osman Hatipoğlu, (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate polysomnography findings and risk factors for sleep-disordered breathing in patients with systemic sclerosis (SSc). Patients and methods: Thirty-nine patients (2 males, 37 females; mean age: 51.1±12.5 years; range, 21 to 76 years) who attended to the Rheumatology Clinic of Trakya University Medical Faculty between March 2014 and May 2014 were included in the study. Thoracic computed tomography, pulmonary function tests, carbon monoxide diffusion tests, echocardiography, and all-night polysomnography in a sleep laboratory were performed in all patients. Demographic and clinical characteristics of the patients were recorded. The Apnea-Hypopnea Index (AHI) scores were calculated. Disease activity was examined using the Medsger Disease Severity Scale (MDSS). Possible risk factors for sleep-disordered breathing were evaluated. Results: Using the AHI of ≥5 for obstructive sleep apnea (OSA), 21 (53.8%) of the patients were classified as having OSA. There were no significant differences between the groups with and without OSA in terms of steroid use (p=0.4), CT involvement (p=0.3), and Warrick (p=0.6) and MDSS scores (p=0.5). Age, body mass index (BMI), and mean oxygen desaturation index were found to be significant in the univariate analysis (p<0.1); however, the multivariate analysis revealed only BMI as significant risk factor of OSA (p=0.028). In the multivariate analysis, the mean saturation was found to be significant risk factor for high pulmonary artery pressure (p<0.001). Conclusion: Although OSA is common in SSc, only increased BMI is a significant risk factor of OSA, but not lung involvement, Warrick scores, or MDSS scores.